Short term negative effect of oxalic acid in Apis mellifera iberiensis - Martín-Hernández, R.; Higes, M.; Pérez, J.L.; Nozal, M.J.; Gómez, L.; Meana, A. (Spanish Journal of Agricultural Research, 2007)
The toxic effect of oxalic acid (OA) on Apis mellifera iberiensis was studied using field and laboratory assays. Bee deaths were higher in OA treated hives than in control hives. Pathological repercussions of topical application of 10% OA were observed in different internal honeybee organs. After 24 h, there were severe alterations in the ventricular epithelial layer while by 48 h there was clearly seen degeneration of the rectal epithelium. Irreversible lesions appeared at 48 h in different bee organs with increased cellular damage after 72 h. Indications are that the effect of the OA continues after initial contact and causes permanent lesions in digestive and excretory organs. Tissue distribution of the acid in different bee organs, after topical administration, suggests that some of the acid is ingested, in some way, by the bee.